Downstream process design for microalgae - Sindri Freyr Ólafsson 1988- (2013)
Various species of microalgae have been cultured through the years but the culturing conditions and downstream process can be very different between cases. In the current thesis a downstream process is designed for two types of microalgae, Dunaliella salina and Chlorella vulgaris. Dunaliella salina is chosen due to its high β-carotene production, it is cultured in a photobioreactor under specific conditions to increase growth and β-carotene production. Natural β-carotene products are in the price range $275-$2,750 per kg, making it an interesting choice of product to sell. Chlorella vulgaris is often used in health nutrition and is sold for $46 per kg. A downstream process for microalgae consists of one or more of the following steps: harvesting/dewatering, cell disruption, drying and extracting. Methods for each step are reviewed and eventually the most suitable methods and equipment are used in the downstream process design. A cost analysis is done for the downstream process designs. The cost analysis shows that a downstream process of microalgae in Iceland has a great potential. Margar tegundir smáþörunga hafa verið ræktaðar í gegnum tíðina en ræktunaraðstæður og framleiðsluferli geta verið mismunandi á milli verkefna. Þessi ritgerð tekur fyrir hönnun á framleiðsluferli fyrir tvær tegundir af smáþörungum, Dunaliella salina og Chlorella vulgaris. Dunaliella salina varð fyrir valinu vegna hæfileika til mikillar β-karótín framleiðslu, ræktunin fer fram í ljóslífrænu hvarfrými (e. photobioreactor) undir sérstökum aðstæðum sem stuðla að auknum vexti og β-karótín framleiðslu. Náttúrulegar β-karótín vörur eru verðlagðar á bilinu $275-$2.750 á kg, þessi háa verðlagning gerir vörurnar áhugaverðar til sölu. Chlorella vulgaris er oft seldur á heilsumarkað fyrir $46 á kg. Framleiðsluferli fyrir smáþörunga samanstendur af einu eða fleiri af eftirtöldum þáttum: Einangrun á smáþörung úr vatni/afvötnun, frumusundrun, þurrkun og útdrætti. Fjallað er um vinnsluaðferðir innan þessara þátta og að lokum eru viðeigandi aðferðir ...